2021
DOI: 10.1111/rec.13540
|View full text |Cite
|
Sign up to set email alerts
|

A life‐of‐mine approach to fauna monitoring is critical for recovering functional ecosystems to restored landscapes

Abstract: Mineral extraction activities are intensely disruptive to ecosystems and their associated fauna. Few countries globally have comprehensive legislation surrounding mine site restoration, but within Australia, restoration of discontinued mine sites is a legislative requirement. However, substantial ambiguity regarding the optimal techniques for restoring biodiverse and functional fauna assemblages remains, and monitoring activities typically focus on vegetation communities despite functioning ecosystems being re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
3
0
1
Order By: Relevance
“…The common assumption underpinning translocation and restoration biology is that the return of floristic diversity, and provision of basic habitat structures, such as vegetation and logs, will lead to the return of fauna on their own [ 87 ]. However, research has found that whilst this may be a useful first step in the recreation, or selection, of a translocation site or area for recolonisation, this hypothesis on its own can be unreliable due to the complexity of faunal ecological requirements [ 88 , 89 , 90 , 91 ]. As such, a more specific understanding of key limiting factors to the successful establishment of many fauna species at a release site or restored area is vital.…”
Section: Significance Of the Research Programmentioning
confidence: 99%
“…The common assumption underpinning translocation and restoration biology is that the return of floristic diversity, and provision of basic habitat structures, such as vegetation and logs, will lead to the return of fauna on their own [ 87 ]. However, research has found that whilst this may be a useful first step in the recreation, or selection, of a translocation site or area for recolonisation, this hypothesis on its own can be unreliable due to the complexity of faunal ecological requirements [ 88 , 89 , 90 , 91 ]. As such, a more specific understanding of key limiting factors to the successful establishment of many fauna species at a release site or restored area is vital.…”
Section: Significance Of the Research Programmentioning
confidence: 99%
“…Mining is intensely disruptive to ecosystems and their associated fauna; however, mine site restoration monitoring activities typically focus on vegetation communities despite functioning ecosystems being reliant on key trophic interactions involving fauna. Cross et al (2022) argue for a life‐of‐mine approach to fauna monitoring, and that recognizing, quantifying, and monitoring the impacts of mining activities and subsequent restoration on fauna is vital to understanding how anthropogenic disturbances affect natural ecosystems, and in assisting in the successful recovery of ecosystem functionality.…”
Section: Fauna Recoverymentioning
confidence: 99%
“…Además, se debe registrar la sobrevivencia, el diámetro y la altura durante al menos los primeros dos años, ya que estas mediciones pueden predecir el desempeño a mediano plazo (Martínez-Garza et al, 2016). Los monitoreos deben registrar la estructura, el comportamiento y el papel ecológico de las distintas especies que colonicen el sitio, así como el retorno de comunidades faunísticas funcionales, resilientes y biodiversas relacionadas con los paisajes restaurados después de la minería y su seguimiento debe ampliarse hacia un examen holístico (Cross et al, 2021).…”
Section: Actaunclassified